The Secret Life of Evie Hamilton - Alliott, Catherine (London Reader's Digest Ltd.)
"Evie Hamilton has a secret ... one she doesn't even know about. Yet . . .Evie's an Oxfordshire wife and mum who's biggest worry in life is whether or not she can fit in a manicure on her way to fetch her daughter from clarinet lessons. But she's blissfully unaware that her charmed and happy life is about to be turned upside-down. For one sunny morning a letter lands on Evie's immaculate doormat. It's a bombshell, knocking her carefully arranged and managed world completely askew and it threatens to sabotage all she holds dear. What will be left and what will change forever? Is Evie strong enough to fight for what she loves? Can her entire world really be as fragile as her best china?"--Provided by publisher.
Include Illustration
Keywords: Middle-aged mothers -- Catholic women -- Life change events